Dysregulation of metabolic pathways in a mouse model of allergic asthma. Issue 9 (29th March 2017) - Quinn, K. D.; Schedel, M.; Nkrumah‐Elie, Y.; Joetham, A.; Armstrong, M.; Cruickshank‐Quinn, C.; Reisdorph, R.; Gelfand, E. W.; Reisdorph, N.
Abstract: Background: Asthma is a complex lung disease resulting from the interplay of genetic and environmental factors. To understand the molecular changes that occur during the development of allergic asthma without genetic and environmental confounders, an experimental model of allergic asthma in mice was used. Our goals were to (1) identify changes at the small molecule level due to allergen exposure, (2) determine perturbed pathways due to disease, and (3) determine whether small molecule changes correlate with lung function. Methods: In this experimental model of allergic asthma, matched bronchoalveolar lavage (BAL) fluid and plasma were collected from three groups of C57BL6 mice (control vs sensitized and/or challenged with ovalbumin, n=3‐5/group) 6 hour, 24 hour, and 48 hour after the last challenge. Samples were analyzed using liquid chromatography‐mass spectrometry‐based metabolomics. Airway hyper‐responsiveness (AHR) measurements and differential cell counts were performed. Results: In total, 398 and 368 dysregulated metabolites in the BAL fluid and plasma of sensitized and challenged mice were identified, respectively. These belonged to four, interconnected pathways relevant to asthma pathogenesis: sphingolipid metabolism ( P =6.6×10 −5 ), arginine and proline metabolism ( P =1.12×10 −7 ), glycerophospholipid metabolism ( P =1.3×10 −10 ), and the neurotrophin signaling pathway ( P =7.0×10 −6 ). Furthermore, within the arginine and proline metabolism pathway, a positive correlation between urea‐1‐carboxylate and AHR was observed in plasma metabolites, while ornithine revealed a reciprocal effect. In addition, agmatine positively correlated with lung eosinophilia. Conclusion: These findings point to potential targets and pathways that may be central to asthma pathogenesis and can serve as novel therapeutic targets.